Oxysterols suppress constitutive fibrinogen expression - Xia, Hui; Redman, Colvin M. (Thrombosis and Haemostasis, 2003)
Elevated levels of both fibrinogen and cholesterol are risk factors in coronary artery disease. Previously we reported a metabolic link between fibrinogen and lipid metabolism in that HepG2 cells that were programmed by transfection of Bβ-fibrinogen cDNA to overexpress fibrinogen exhibited increased synthesis of cholesterol and increased secretion of apolipoprotein B. In this study we demonstrate that oxysterols, which participate in maintaining cholesterol homeostasis, also down regulate fibrinogen expression. Treatment of HepG2 cells with 25-hydroxycholesterol lowered fibrinogen Aα, Bβ and γ mRNA levels and inhibited fibrinogen synthesis and secretion but had no effect on α1-antitrypsin which, like fibrinogen, is an acute-phase protein. The inhibition of fibrinogen synthesis by oxysterols was maintained in interleukin-6 treated cells. Other oxysterols, that inhibit cholesterol synthesis by a feedback mechanism, also diminished fibrinogen expression in HepG2, rat H-4-II-E hepatoma cells and in primary human hepatocytes. Overexpression of SREBP-1 and SREBP-2 by transfection of HepG2 cells, or treatment with a synthetic LXRα agonist, which affect cholesterol metabolism, did not affect fibrinogen expression. We conclude that fibrinogen and cholesterol may share a novel common regulatory pathway.
Keywords: Fibrinogen; cholesterol; oxysterols